How to give feedback on professionalism in clinical education: A narrative review - Shiva Khayyati Motlagh Bonab; Aeen Mohammadi; Sevda Fazlizade; Elnaz Hashemzadeh; Reyhaneh Golbaf; Hojjat Torkmandi; Mohammad Abdi (Kerman University of Medical Sciences, 2023)
Background: Professionalism means understanding a profession and introducing it to the society through professional behaviors. In particular in clinical settings, constructive feedback is provided in education to create professional behaviors.Objectives: This study aimed to investigate giving feedback on professionalism in clinical education.Methods: A narrative review was conducted in PubMed and Google Scholar on the publications over the last 10 years. Eight hundred twenty-six articles were found in the first step, among which 30 were handed over to the expert panel. Fifteen of 30 articles were finally selected.Results: The data of the studies were in four categories: feedback techniques, feedback in. curriculum, the scope of feedback, and feedback outcome. Feedback on professionalism was mostly presented through online services, portfolio, video-based systems, by a preceptor or peers, longitudinally in internship courses, and Multi Source Feedback (360 degree). In a study, feedback on professionalism was considered formally in the curriculum. Educational experts give both formative and summative feedback (most of which were formative). Based on the literature, feedback can enhance learning professionalism, curriculum reforms, system support, student comfort, evaluations, and efficacy of professionalism.Conclusion: Multi-Source feedback assessment was the most used tool for giving feedback in professionalism, and the most popular form was informal-formative feedback. Since professionalism is a multidimensional concept related to personal communication, multi-source tools have been the most commonly used in the literature.